THE PROBLEM OF ARTHRITIS IN THE MAYAN MUNICIPALITY OF CHANKOM, MEXICO: A SITUATIONAL ANALYSIS FOR DEVELOPING A COMMUNITY-BASED REHABILITATION PROGRAM - Loyola-Sanchez, Adalberto (My University, 2015)
Disability and arthritis in Mexico are important public health problems. There is a need to develop rehabilitation interventions aimed at reducing the prevalence and disabling effects of arthritis in low socioeconomic communities in this country. This thesis reports findings from the initial execution of a mixed-methods participatory research program. This program was designed to develop, implement and evaluate a community-based rehabilitation program to decrease disability of people living with arthritis in the municipality of Chankom, a low-income rural Mayan community located in Southeast Mexico. Epidemiologic results showed a high prevalence of arthritis in Chankom associated with low levels of wealth and high body mass index. In addition, arthritis was associated with a higher prevalence of disability in this municipality. Further results showed that people who live with osteoarthritis in Chankom perform standardized and real-life activities with significant levels of disability. This disability was associated with levels of wealth, pain, muscle strength, self-efficacy, and physical activity. Ethnographic results showed that: a) arthritis reduces the health-related quality of life of people in Chankom through a process of disablement, b) people living with arthritis need access to culturally sensitive healthcare, and c) there are availability, attainability and acceptability barriers to accessing culturally sensitive health services in this municipality, which result from power imbalance between indigenous and non-indigenous people. The work presented in this thesis is the extensive examination of the problems associated with arthritis in Chankom, using quantitative and qualitative methods. Our findings justify the need to develop health policies and interventions to prevent and decrease the disabling effects of arthritis in this marginalized community. Moreover, these findings will support the creation of a culturally sensitive, community-based rehabilitation program, as a multi-level strategy to promote social development and improve health-related quality of life of people living with arthritis in the municipality of Chankom.
A SITUATIONAL ANALYSIS OF ARTHRITIS IN CHANKOM
Keywords: Community based rehabilitation; Indigenous populations; Mexico; Mixed Methods; Participatory Action Research; Mexico